HUBUNGAN ANTARA KECEPATAN AWALAN DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI GAYA FLOP PADA SISWA PROGRAM EKSTRAKULIKULER SMAN 2 PANDEGLANG - Rhamadhan, Alfaiz Zikri (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2022)
This study uses Research & Development development research that will produce a product in the form of a training model. The goal to be achieved in this study is to create a futsal balance skill-based passing training model through new forms of play, in accordance with the characteristics of the research targets in SMP Nurul Iman students. This study created a product design of 20 training models then the final results with expert justification tests became 20 training models with 10 training models using bosu balls and 10 training models using gym balls. Based on the validation test used is the justification test of experts in the field of futsal. The purpose of this study is as a reference material or reference to improve skills, success and provide variations in passing training using bosu balls and gym balls during training situations.